Book Review - Ranelagh, John; Blum, William; Prados, John; Woodward, Bob; Carnesale, Albert; Haass, Richard N.; Luttwak, Edward N.; Lebow, Richard N.; Berkowsky, Pamela B. ; Dyker, David A.; Fairbank, John King; Joffe, Ellis; Ramos, Joseph; Thorp, Rosemary; Whitehead, Laurence; Sharp, Margaret; Shearman, Claire; Deyo, Frederick C.; Conybeare, John A. C. (Tufts Archival Research Center, 2005)
Volume 12, Issue 1. Winter. The Agency: The Rise and Decline of the CIA from Wild Bill Donovan. The CIA: A Forgotten History . Presidents' Secret Wars: CIA and Pentagon Covert Operations Since World War II. Veil. The Secret Wars of the CIA . Superpower Arms Control: Setting the Record Straight . Strategy: The Logic of War and Peace . Nuclear Crisis Management . Containing the Soviet Union: A Critique of U.S. Policy. The Soviet Union Under Gorbachev: Prospects for Reform . China Watch . The Chinese Army After Mao . Neoconservative Economics in the Southern Cone of Latin America, 1973-1983. Latin American Debt and the Adjustment Crisis . European Technological Collaboration . The Political Economy of the New Asian Industrialism . Trade Wars: The Theory and Practice of International Commercial Rivalry. Book Review